The effects of clavulanic acid and amoxicillin on cue-primed reinstatement of cocaine seeking - Bechard, Allison R. (Behav Neurosci, 2019)
Research using the cocaine self-administration and reinstatement animal model of relapse finds that the beta-lactam antibiotic, ceftriaxone, attenuates cocaine-primed reinstatement of cocaine seeking and upregulates two proteins that regulate glutamate release and reuptake (xCT and GLT-1, respectively) in the nucleus accumbens core (NAc). We tested three compounds with beta-lactam rings for their ability to attenuate cue-primed reinstatement and increase GLT-1 and xCT expression in the NAc and prefrontal cortex (PFC). Rats self-administered intravenous cocaine for 1 hr/day for 7 days then 6 hrs/day for 10 days. Cue-primed reinstatement tests began after 8–10 days of extinction training. Rats received oral vehicle, clavulanic acid (CA), amoxicillin (AMX), or CA+AMX (Augmentin; AUG) for 5 days prior to testing. Only AMX-treated rats demonstrated a reduction of cocaine-seeking that trended towards significance, warranting future investigation of a wider range of doses. In the NAc, GLT-1a expression was reduced in vehicle-treated rats relative to cocaine-naïve controls and was not restored by AMX or AUG. CA-treated rats reinstated more than vehicle-treated rats and exhibited GLT-1a and xCT expression intermediate between cocaine-naïve controls and vehicle-treated cocaine rats. In agreement with our previous work, cocaine did not decrease PFC GLT-1a expression. Cocaine reduced xCT expression in the PFC that was unchanged by any of the three compounds. These results indicate that AMX may be another beta-lactam that attenuates cocaine relapse. Furthermore, the upregulation of both GLT-1 and xCT in the NAc may be needed to attenuate cocaine seeking.